STRUCTURE GENETIQUE DES POPULATIONS D’ANOPHELES NILI S.S VECTEUR DU PALUDISME EN MILIEU RURAL ET PERIURBAIN DE COTE D’IVOIRE - Adja, Akre Maurice; Toure, Mahama; Kengne, Pierre (European Scientific Journal, ESJ, 2015)
In Côte d’Ivoire, the Anopheles nili s.s species plays an important role in malaria transmission. However, the transmission of malaria by the populations of An. nili s.s in different regions of Côte d’Ivoire exhibits heterogeneous patterns. The study was initiated to find out whether the diversity of malaria vectorial transmission with An. nili s.s from different regions was linked to a heterogeneity of these species populations in Côte d’Ivoire. To better conduct this study, 134 individuals of An. nili s.s mosquitoes were obtained from a human landing collection and a study on the structure of the populations was carried out by isoenzyme analysis of 7 loci (IDH1, IDH2, PGI, GOT, ME, MDH, PGM). The study sites include Ganse (rural, shrubby savannah), Gbatta, Gouliako (rural, forest zone), Nambekaha (rural, Sudanian savannah), and Kpehiri (peri-urban, forest zone). The An. nilis.s populations in Côte d’Ivoire have on average 1.5 to2.5 alleles per locu and were at Hardy–Weinberg equilibrium. The comparison of the populations shows over the 7 loci, no significant difference between the pairs of populations. The comparison of the An. nili s.s populations from Kpehiri to that of Ganse shows over all loci a significant difference (Fst = 0,1086 ; P= 0,0147). The structure of the An. nili s.s populations in Côte d’Ivoire is not linked to the distribution of the large vegetal groups (forest, shrubby savannah Sudanian savannah). Yet, there is a difference between the Ganse population, in a rural zone, located close to the Comoe National Park and that of Kpehiri in the peri-urban area.